The Psychological Costs of Citizen Coproduction. (30th January 2020) - Thomsen, Mette Kjærgaard; Baekgaard, Martin; Jensen, Ulrich Thy
Abstract: Coproduction where citizens collaborate with public employees in producing and delivering public services is often argued to be associated with benefits for either participating citizens, their relatives, friends, or society at large. Less is known about the potential downsides associated with citizen participation in coproduction of public services. We argue that psychological costs, such as experiences of stigma, stress, and loss of autonomy may arise among citizens in response to coproduction initiatives stimulated or directly imposed by public organizations. We test our propositions in two randomized vignette experiments on a representative sample of Danish citizens. First, we manipulate whether citizens are encouraged to coproduce public services yielding private or collective benefits. Second, we induce perceived self-efficacy among a subsample of citizens. We find that citizens are more likely to experience psychological costs when they are encouraged to coproduce public services resulting in private benefits for relatives or friends in contrast to collective benefits for a larger group of people. Furthermore, these psychological costs are felt to a greater extent among citizens with low self-efficacy. Fusing insights from multiple perspectives, our study pushes the theoretical frontiers of coproduction literature by illustrating how complex emotional responses is an overlooked, but integral part of a more comprehensive theory on the manifestations and effects of citizen coproduction.